2018
DOI: 10.1186/s12891-018-1961-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis knowledge and beliefs in diabetic patients: a cross sectional study from Palestine

Abstract: BackgroundOsteoporosis is a potential metabolic complication of diabetes mellitus (DM). Therefore, patients with DM should have adequate osteoporosis knowledge and beliefs in order to get engaged in osteoporosis preventive behaviors. The objective of this study was to assess osteoporosis knowledge and beliefs among diabetic patients.MethodsThis was a cross sectional study carried out at Al-Makhfiah governmental primary healthcare unit in Nablus, Palestine from September 2016 to December 2016. The tools used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The care of individuals living with diabetes is standardized across Ireland, indicating generalisability across the country. Further, similar studies conducted in China [17] and Palestine [16] indicate the findings presented here remain valid internationally.…”
Section: Limitations Of the Studysupporting
confidence: 82%
See 3 more Smart Citations
“…The care of individuals living with diabetes is standardized across Ireland, indicating generalisability across the country. Further, similar studies conducted in China [17] and Palestine [16] indicate the findings presented here remain valid internationally.…”
Section: Limitations Of the Studysupporting
confidence: 82%
“…This study revealed a low level of awareness and understanding of bone-associated complications of diabetes when participants were asked to A) identify bone fractures or delayed bone healing from a list of potential complications or B) discuss how diabetes may impact bone health. Other published studies have also explored the knowledge of diabetes-related complications in people living with diabetes [20][21][22][23], some focusing on assessing a participant's understanding of diabetic osteopathy [16,17]. The trends identified in this study are comparable to those identified internationally, which is interesting given the multivariate nature of the understanding potentially cofounded by age, gender, geographical localization, availability of educational programmes, country-dependent management of diabetes care, and other societal factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 These scales have been adapted to evaluate and guide the intervention of osteoporosis preventive behaviors in many middle-and low-income countries. [20][21][22][23] Few studies have addressed the level of osteoporosis knowledge and beliefs among nonhealth care professionals in Latin America 11,24 and existing data suggest that osteoporosis knowledge often fails to translate into preventive behaviors among the general population. 25,26 To better understand the level of knowledge, risk factors, and health beliefs regarding osteoporosis in Peru, we conducted an exploratory study among a group of female peer leaders in a Peruvian periurban community.…”
Section: Introductionmentioning
confidence: 99%